Hemodialysis Different Aspects - Goretti Penido, Maria (IntechOpen, 2011)
The book provides practical and accessible information on all aspects of hemodialysis, with emphasis on day-to-day management of patients. It is quite comprehensive as it covers almost all the aspects of hemodialysis. In short it is a valuable book and an essential aid in the dialysis room.